Daur Ulang Sampah Anorganik di Cengkareng Jakarta Barat - Yuliarty, Popy; Utami, Diah; Dwiasnati, Saruni (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2024)
This PkM activity was intended to increase knowledge and skills in managing inorganic waste at partner locations and their surroundings. That problem can be overcome by providing education, understanding the importance of sorting waste from home to public places, for example, at school, providing insight into the value that this waste still has from an economic perspective and providing training in skills to make recycled products from the collected waste. The method for this activity begins with observation at the location, preparation, and implementation in two extensive sessions, namely providing theoretical material and practical material for making recycled products. Participants were asked to fill out a questionnaire to assess their activity. The expected output is a product resulting from recycling plastic wrap waste and showing appreciation to participants for the best-recycled products. Coming from the description of the situation review, the PkM team concluded that there were several problems faced by Mitra, namely: Mitra is a place that has the potential to produce large amounts of inorganic waste because of the enormous of students, and it is located in a very dense residential area, very close together. Also, with the Cengkareng Big Market, efforts need to be made to manage waste, especially inorganic waste, by recycling inorganic waste into value-added products.